The mixed blessing of living together or close by: Parent-child relationship quality and life satisfaction of older adults in China - Ke Shen; Feinian Chen; Hangqing Ruan (Demographic Research, 2021)
Background: Geographic proximity between parents and children is increasingly recognized as an alternative measure to coresidence as a gauge for intergenerational support in China. The quality of intergenerational relationships is another important dimension of intergenerational ties that is often underexplored. Objective: We examine the association between parent-child proximity and life satisfaction of older adults and how it interacts with the quality of intergenerational relationships, particularly for vulnerable subpopulations. Methods: We use data from the China Longitudinal Aging Social Survey (CLASS 2014). We use ordered logit models to predict life satisfaction scores (ranged 1 to 4). Results: Our analyses show that parent-child relationship quality is strongly associated with life satisfaction, regardless of living proximity, in our full sample analysis. For those who have a lower-quality relationship with their children, coresidence or close-distance living does not enhance life satisfaction and they indeed have lower life satisfaction than those parents who have all children living farther away but maintain a high-quality relationship with them. At the same time, for those who have a high-quality relationship with their children, we find that close proximity provides added benefits for the subpopulations who are socioeconomically or physically disadvantaged, that is, female, urban, unmarried, and disabled (in terms of being capable of activities of daily living, or ADL) older adults. Conclusions: We recognize the interdependence of the quality of the intergenerational ties and parent-child proximity in promoting life satisfaction, particularly for subpopulations who are in stronger need of support from adult children. Contribution: Our study clearly points to the importance of extending the research on intergenerational relationship beyond the boundary of the household and of paying close attention to the affective dimension of intergenerational ties.